Isu Kekurangan Tenaga Buruh yang Mempengaruhi Kelewatan Projek Pembinaan Lebuh Raya Pan Borneo Sarawak - Rubin, Urai; Shafii, Haryati; Masrom, Md. Asrul Nasid; Ismayatim, Norddin (Research in Management of Technology and Business, 2024)
In order to improve the transport system in the country, especially in the rural area, several highway development projects have been carried out such as the Pan Borneo Highway which aims to improve the quality of the existing road and make it a highway. However, the Pan Borneo Highway construction project is facing delays due to several factors including the lack of manpower to meet the needs of the completion of this highway. Therefore, this study was carried out to achieve three objectives, namely, to identify the factor of labor shortage that delayed the Sarawak Pan Borneo Highway construction project, to identify the effects of labor shortage in the Sarawak Pan Borneo Highway construction project and to study steps to solve the issue of labor shortage in the project the construction of Sarawak's Pan Borneo Highway. This study was conducted using a qualitative method where the data collection instrument used was an interview with 4 respondents consisting of contractors and engineers involved in the Pan Borneo highway project. The analysis method used is thematic analysis. The findings of the study found that the labor shortage factors that cause the labor shortage are covid-19 pandemic factors, skilled labor shortage factors, worker selection factors among local laborers and communication factors. Some of the effects of the labor shortage have affected the delay of this project, which is a decrease in productivity, an increase in overall costs and disrupted economic growth. Meanwhile, there are several steps to solve the labor shortage issue that affects the delay of this project, namely offering more job opportunities to locals and foreigners, improving workers' skills, obtaining allocations from the government and holding local labor development programs. Therefore, this study was conducted to help find out one of the causes of the delay in the Sarawak Pan Borneo Expressway project, which is the lack of labor and to study the effects of the lack of labor in this project.